FORMATION OF ETHICAL CULTURE OF INTENDING EDUCATORS IN THE EDUCATIONAL PROCESS OF HIGHER EDUCATION INSTITUTION - Dmitrenko, Natalia; Voloshyna, Oksana; Budas, Iuliia; Klybanivska, Tetiana (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
The study intends to expand a methodology of shaping intending educators’ ethical culture. The examples of effective techniques that were used in a teacher-training process are provided. Some samples of authentic pedagogical cases created by teachers and students are presented. The main stages of work on the formulation of the “Teacher’s Code of Ethics” are revealed. Such interaction methods as “Brain Storming”, “Decision Tree” are given. Fragments of the lesson “Pedagogical techniques in the structure of pedagogical communication of a teacher” are described, where students analyze videos on pedagogical topics, identify phrases that violate the ethical norms of the teaching profession and choose alternatives.The excerpts from the works of intending educators, where students reflect on the teachers’ functions and responsibilities, are analysed. A structured set of traditional (lectures, tutorials, laboratory classes) and innovative (brainstorming, role-playing, case studies, decision tree, pedagogical marathon, etc.) methods, which accelerate students’ gradual progress to the highest creative level of ethic culture is presented. Such organization of the educational process reflects the developmental changes from intuitive actions in different situations on the basis of initial ethics knowledge to the willingness of intending educators to work independently, guided by high-minded principles and norms in professional situations.